Fishery, biology and stock assessment ofCynoglossus macrostomus (Norman) off Malabarcoast - Manojkumar, P P (Indian Journal of Fisheries, 2011)
Cynoglossus macrostomus formed 93 % of the annual average landings offlatfishes (3951 t) during 1993-2004 at Calicut. The fishery showed annualfluctuations. Peak landings were recorded during December-April. Growthparameters of this species were L! = 164.5 mm y-1 and K = 0.70y-1. The fishgrows to 83, 124 and 146 mm at the end of 1-3 years.Â  The total and naturalmortality were 3.01 y-1Â  and 0.91 y-1 respectively. The length-weight relationshipshows that the growth is isometric and there is no significant variation betweensexes. The spawning is prolonged with two peaks. The length at first maturityis 102 mm. Females dominated the fishery. The stock is exploited marginallybelow the optimum level at present. The total and standing stock of this speciesalong the Calicut coast is estimated as 5430 t and 1720 t respectively.